Hubungan antara Hipoglikemi dengan Kejadian Hipotermi pada Neonatus Rujukan di RSUD Dr. Moewardi - Dio Dara Virgiansari; Dwi Hidayah; Leli Saptawati (Nexus Kedokteran Klinik, 2013)
Neonatal hypoglycaemia is an avoidable cause of mortality and neurodevelopmental impairment. Hypoglicemia may develop to hypothermia as a result of metabolic thermogenesis disturbance. Hypothermia during the newborns period is widely regarded as a major contributory cause of significant morbidity and mortality in developing countries including Indonesia, about 7% prevalence of hypothermia has been reported happens on newborns. The objective of this study was to determine the association between hypoglicemia and hypotermia in newborns. An analytic observational using cross sectional approach was used in this study. A total of eighty one newborns was selected by fixed-disease sampling. Sample of this study were the newborns who referred to Dr. Moewardi Hospital. The data were collected by the measurement of blood glucose concentration and axillary temperature of newborns. The data was analyzed using multiple logistic regression test on SPSS 16 for Windows. Hypoglycemic newborns have a risk of hypothermia 2.381 times higher than non hypoglicemic newborns after controlling some confounding factors, such as: age, birth weight, gestational age, and status of asphyxia, altough it was statistically not significant (OR = 1.98; CI = 95%; 0.54, 7.73; p = 0.305). Early neonatal age (0-7 days), low birth weight (< 2.500 gram), early gestational age (< 37 weeks), asphyxia status were also risk factors of hypothermia in newborns. There was a moderate association between hypoglicemia and hypothermia on referral newborns, altough it was statistically not significant. Hypoglycemic newborns have a higher risk of hypothermia than non hypoglicemic newborns after controlling some confounding factors, such as: age, birth weight, gestational age, and status of asphyxia. Keywords: newborns, referral, hypoglicemia, hypothermia